STRATEGI PENGELOLAAN PENGGUNAAN AIR DI PONDOK PESANTREN IMAM AN NAWAWI DALAM MENDUKUNG KONSERVASI AIR DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Ucin Muksin; Suwondo Suwondo; Imam Suprayogi (Jurnal Ilmu Lingkungan, 2021)
Research of strategy for water use management at The Imam An Nawawi Islamic Boarding School in supporting water conservation in Kulim Village, Tenayan Raya District, Pekanbaru City has been completed. The purpose of this research is to see the behavior of water use, the policy of the management of the boarding school, to analyze the economic impact due to the behavior of water use and to design a water use management strategy in the Imam An Nawawi Islamic Boarding School in supporting water conservation. To find out the behavior and policy was carried out through interviews and field observations. The economic impact is calculated by comparing the volume of water used against the water use standard. The resulting strategy is compiled using a SWOT analysis. The behavior of the santri in wasting water is still quite high (55%) and must be supported by a policy from the management of Islamic Boarding School. The economic potential of water use behavior can be reduce of PLN payment costs up to 65% of the total PLN cost of Rp. 3.6 million per month. With the SWOT analysis, 9 strategies can be implemented in water use management to support water conservation.